O PIBID como espaço de pesquisa no processo de formação de professores de química - Costa, Kátia Maria Guimarães (2017)
This study aimed to understand in which aspects the development of a PIBID with research can contribute to the initial training of chemistry teachers. It was realized with students in initial formation of degree of Chemistry of the Federal Institute of Education, Science and Technology of the Amazonas - IFAM, participants of Project Uirapuru, that represents in IFAM, the Institutional Program of Initiations to Teaching – PIBID. For the development of the study, research-action was assumed as a methodological research strategy. In the first phase, two movements were necessary, beginning with the pre-diagnostic meetings that took place at the IFAM and aimed at an approximation with the graduates and the presentation of the proposal, explaining that they would walk a path of doing research, researching their teaching. The second movement was the insertion of the students in the three partner schools, effecting the diagnostic phase and the creation of the investigative teams formed by the students in initial formation, the school teacher and the researcher. In the next phase, starting from the problematic identified in the diagnostic phase, its research and intervention/research projects were elaborated, which in the sequence were implemented and evaluated, having in the reflexive process, action-reflection-writing, the central element for the construction and production of knowledge. The set of data that were constructed during this walk, through audio and video recordings, field notes, reflexive diaries and research reports, were constituted in the corpus of the research and were treated by the Discursive Textual Analysis (ATD). The analysis revealed that experiencing the daily reality of the school were involved in a process developed from the construction of an intentionally planned and reflective course, in which they investigated their practices and built their own knowledge of teaching that made possible changes in their effective practices in the classroom. class; also made it possible to define identity characteristics for the graduates; and yet, the construction and production of knowledge are potentialized within a collective process, through an action-reflection-writing movement. These aspects show that the PIBID with research contributed to the professional and autonomous development of the participating graduates, future teachers of chemistry.